2014
DOI: 10.1002/etc.2720
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthesis, chlorophyll fluorescence characteristics, and chlorophyll content of soybean seedlings under combined stress of bisphenol A and cadmium

Abstract: Bisphenol A (BPA) is ubiquitous in the environment because of its continual application in plastics and the epoxy resin industry. Cadmium (Cd) is a highly toxic heavy metal element mainly used in smelting, electroplating, and plastic and dye manufacturing. Pollution as a result of BPA and Cd exists simultaneously in many agricultural regions. However, little information is available regarding the combined effects of BPA and Cd on plants. The combined effects of BPA and Cd on the photosynthesis, chlorophyll flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(29 citation statements)
references
References 35 publications
3
26
0
Order By: Relevance
“…Chlorophyll fluorescence technology can reflect the process of light energy absorption and transmission during photosynthesis, so it is a fast, non-invasive probe for measuring photosynthetic function in leaves. The quantum efficiency of PSII and the extent of photoinhibition are continually used to ensure the energy distribution state in the thylakoid membrane (Hu et al 2014;Zhang et al 2015). The most vital chlorophyll fluorescence parameters are F v /F m , ETR, NPQ, q P , and 1-q P values, and they are broadly applied to plant stress physiology studies (Baker and Rosenqvist 2004;Olvera-González et al 2013;Thwe et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Chlorophyll fluorescence technology can reflect the process of light energy absorption and transmission during photosynthesis, so it is a fast, non-invasive probe for measuring photosynthetic function in leaves. The quantum efficiency of PSII and the extent of photoinhibition are continually used to ensure the energy distribution state in the thylakoid membrane (Hu et al 2014;Zhang et al 2015). The most vital chlorophyll fluorescence parameters are F v /F m , ETR, NPQ, q P , and 1-q P values, and they are broadly applied to plant stress physiology studies (Baker and Rosenqvist 2004;Olvera-González et al 2013;Thwe et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, values of individual leaves within a plant are usually compared indirectly-for example, by studying plant responses to leaf removal [40] or by measuring net photosynthetic rates of individual leaves [41], i.e., by using approaches that are much more labour intensive than chlorophyll fluorescence measurements. In this study, we used the maximal photochemical efficiency (F v /F m ) as a proxy for the photosynthetic value of a leaf, because the photochemical efficiency is positively correlated with the net photosynthetic rate across a range of experimental conditions [42]. We acknowledge that our proxy does not provide full information on the net photosynthetic rate, and we are aware of the pitfalls and caveats of the chlorophyll fluorescence method (outlined, e.g., in [43]), as well as of studies that failed to find correlations between the maximal photochemical efficiency and net photosynthetic rate [44].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, a lowered F v /F m , when it is measured after an appropriate period of dark adaptation, is commonly regarded as a good indicator of a sustained impairment of photochemistry [45]. This index is still widely used in ecological, environmental and agricultural research to quantify stress in plants [42,46,47]. Surprisingly, the relationship between chlorophyll fluorescence and leaf FA was the opposite of what we had expected, as the photochemical efficiency was higher in more asymmetric leaves than in less asymmetric leaves.…”
Section: Discussionmentioning
confidence: 99%
“…It has long been demonstrated that the disruption of chloroplast function has a profound effect on chlorophyll biosynthesis and stability [6,8]. In addition to its role in photosynthesis, chloroplast is also involved in the biosynthesis of hormones, sugars and amino acids.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, disruption of the Chl synthase encoding gene (YGL1) leads to decreased Chl contents and delayed chloroplast development, resulting in a yellow-green leaf phenotype in young plants in rice [2]. Chl content in plants can be influenced by both external and internal factors such as light, salt, osmotic stress and leaf age due to alterations in the genes expression or post-translational modification of proteins involved in Chl synthesis and Chl degradation [6][7][8][9][10]. For example, a missense mutation of the fructose-1,6-bisphosphatase (FBPase) encoding gene results in a yellow-green leaf phenotype and severe growth retardation in rice [11].…”
Section: Introductionmentioning
confidence: 99%